Síntesis de mono di tri acetil gliceroles a partir de glicerina grado técnico - Delgado Tobón , Arnoldo Emilio; Rodríguez Carmona, Esperanza (TECCIENCIA, 2020)
Mono, di, tri acetyl glycerols (MDTAG) were synthesized from technical grade glyc- erin , as an alternative for the use of glycerol generated by the biodiesel industry. The esteriﬁcation, was done using molar ratio (acetic acid: glycerin 1:6), at labora- tory scale, toluene was added as a dragging agent to periodically remove the water of the reaction. Ion exchange resin was used as a heterogeneous catalyst. MDTAG were characterized using infrared spectroscopy (FT-IR). The low temperature be- havior was analyzed by means of diﬀerential scanning calorimetry (DSC). MDTAG obtained experimentally showed excellent performance at temperatures below 0 °C. This result makes MDTAG potentially considered as additives to improve the low-temperature ﬂuidity of biolubricant bases (from modiﬁed vegetable oils).